Apprenticeship input demand cyclicality of R&D and non-R&D firms - Mühlemann, Samuel [Verfasser]; Pfann, Gerard A. [Verfasser]; Pfeifer, Harald [Verfasser] (My University, 2024)
„For centuries, the flexibility to hire and train apprentices has been an important source of successful implementation of innovations in production technologies. This paper shows that the input flexibility of apprenticeships in German firms is associated with product innovation. Even though R&D firms face higher costs to set up training facilities and are therefore less likely to start up apprenticeship training than non-R&D firms, conditional on having invested set up costs, R&D firms train more than non-R&D firms. R&D firms that train apprentices are more responsive to cyclical fluctuations. Against the trend of a 0.5 percentage points annual decline of new productsintroduced in the market, firms that train and expand their training activities through time are primarily responsible for an increase in product innovation. R&D firms also renew products 2.7 times more than non-R&D firms. All this emphasizes the prime role of firms that train apprentices in reinvigorating the economy.“ (authors‘ abstract; BIBB-Doku)
Keywords: S 3.2 Unternehmen und Behörden; G 1.3.1.1 Ausbildungsstellenmarkt; 370; 330; Betrieb; Forschung und Entwicklung; Innovation; Produktionstechnik; Ausbildungsverhalten; Ausbildungsbereitschaft; Kosten; Berufsausbildung; Bildungsfinanzierung